Pakistan : A Hard Country - Lieven, Anatol (UK : Penguin UK, 2012)
DAILY TELEGRAPH and INDEPENDENT BOOKS OF THE YEAR LONGLISTED FOR THE ORWELL PRIZE 2012 2011 LOS ANGELES TIMES BOOK PRIZE FINALIST In the wake of Pakistan's development of nuclear weapons, unpoliceable border areas, shelter of the Afghan Taliban and Bin Laden, and the spread of terrorist attacks by groups based in Pakistan to London, Bombay and New York, there is a clear need to look further than the simple image of a failed state so often portrayed in the media, and to see instead a country of immense complexity and importance. Lieven's profound and sophisticated analysis paves the way for clearer understanding of this remarkable and highly contradictory country.
International Edition.
Keywords: History--Pakistan; Social conditions; Politics and government; Political culture; Strategic aspects of individual places; Political science; Social history